Analysis of Algebra Communication Skills and Creative Thinking Skill Levels: In Terms of Cognitive Style - Wieka Septiyana; Ramzil Huda Zarista; Roudotul Hasanah (AlphaMath : Journal of Mathematics Education, 2023)
The students have difference in cognitive style. This research aimed to describe and analyze students’ communication skills and creative thinking skill level in view of field dependent and independent cognitive style on algebraic concept. Algebra communication skill is essential skill needed for solving mathematical problems. Algebra must be mastered by the students because related to other materials. Algebra topic analyzed in this study is quadratic equation word problems. The indicators of communication skill include (1) able to state the situation into mathematical notations, structures or symbols, (2) able to demonstrate and describe unique algorithms in problem solving, and 3) able to construct and explain real-world phenomena in graph, sentence, equation, table or other presentation. The student level of creative thinking skill can be seen from fluency, flexibility and novelty. This research used a mixed-method. The object were 16 students of junior high school in Tangerang. The data collection techniques used test and interview. Cognitive styles are grouped using the Group Embedded Figure Test (GEFT) which divide the students into field dependent (FD) and field independent (FI). The results of the study indicated that algebra communication skill of students with FD and FI were not different significantly in problem solving. Both are able to understand the problems into mathematical expressions, but not all groups state the correct mathematical equations. The students used different strategy to solve the problems. FD students used less detailed strategy, incomplete analysis, think generally, and not quite precise in writing mathematical equations, while FI students provided detailed explanations, better accuracy, think more flexibly, and state mathematical equation precisely. In general, they have same creative level.